PENGARUH PENGETAHUAN DAN PROMOSI TERHADAP PREFERENSI PEDAGANG DALAM MEMILIH JASA PERBANKAN SYARIAH (STUDI KASUS PASAR PADANG TUJUH KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT) - Suci Putri Yani; Amsah Hendri Doni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Judging from the majority of people in West Pasaman Regency embracing Islam, Islamic banks should be the top priority for Muslim communities in making transactions, saving, and obtaining capital. However, in reality in the field, people prefer conventional banks to Islamic banks, especially Padang Tujuh market traders. The knowledge of Padang Tujuh market traders is still low due to not often getting information regarding Islamic banks and the lack of promotions set by Islamic banks, whether directly or indirectly, related to products as well as services available. This research is intended with the aim of measuring how much knowledge and promotion affect traders' preferences in choosing Islamic banking services. This research is a study employing quantitative descriptive methods. It utilizes both primary and secondary data. The study population includes traders from the Padang Tujuh market, with a sample of 57 respondents gathered through observation, interviews, and questionnaires. The data processing involves testing the research instruments, which includes validity and reliability tests, as well as classical assumption tests such as normality, autocorrelation, multicollinearity, and heteroscedasticity tests. Additionally, multiple linear regression tests, coefficient of determination tests, and hypothesis testing using t-tests and f-tests were conducted. This study determined that the knowledge variable has a value of 0.049, which is below 0.05 (0.049 < 0.05). Therefore, it can be concluded that the knowledge variable has a significant partial effect on preferences. The promotion variable also showed significant results (0.00 < 0.05), indicating that it has a significant partial effect on preferences as well. When considered simultaneously, knowledge and promotion variables yielded an F count of 37.650, exceeding the F table value of 4.020. Consequently, it is concluded that both knowledge and promotion collectively have a significant impact on preferences.